If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 3 = 4 Reorder the terms: 3 + 2w = 4 Solving 3 + 2w = 4 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2w = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 2w = 4 + -3 2w = 4 + -3 Combine like terms: 4 + -3 = 1 2w = 1 Divide each side by '2'. w = 0.5 Simplifying w = 0.5
| ln(x-3)=ln(2) | | 3x/2+1=11/2 | | 111-3x=24x+24 | | y=5/2x+6 | | 7x-2x+4-5=3x-1 | | x-60=-17/2(y-20) | | 8p-p+14=1-6p | | 7x+3*(2x-4)=0 | | 2x+3x+7=-43 | | 2(v+8)=9v-47 | | -10=-8v+2(v-8) | | 18+16-5+4= | | -1=-8+x/-2 | | -16y(y-18)= | | 6(x-11)=x+9 | | 2.5k+5-1.5k=14 | | a/-3+3=8 | | z=5-28z | | 7(3m-5)-5(1+m)=0 | | 0=-16t^2+20t+24 | | x^3+x^2-12x-10=0 | | x/23=0.5 | | 55-6(3b-1)=-11 | | x/23=50 | | 9X1/2=38 | | 16y-8xy+yx^2=0 | | 4y-8y=5 | | 13=4x-9 | | 4+x=5x | | -131=-8(m+7)-7m | | 3(d-8)-5=9(9d+2)+1 | | -105=6(3r-4)-9r |